Sustainability Assessment of Integrated Pest Management Rice Farms to Enchange Food Security in Kediri District - Rita Parmawati; Setyo Widagdo; Soemarno Soemarno; Supriyanto Supriyanto; Indra Purnama Putra; Didik Muktiyanto; Galif Gumelar; Ridwan Danuarta Galisong (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
As one of the regions with the potential to become a national food production center, Kediri District in East Java has initiated the implementation of an organic farming system. To ensure the long-term viability of this agricultural system, it is essential to assess its level of sustainability. The objective of this study is to conduct a sustainability analysis to ascertain the status of sustainability and optimization strategies for IPM rice farming in the district. The research was conducted in Kediri District, with samples of Sugihwaras Village and Pandantoyo Village, involving a total of 100 respondents. These respondents were then interviewed to measure the six dimensions and 51 attributes used in the study. The data was analyzed using Multidimensional Scaling (MDS) RAP-IPM, and a prospective analysis was subsequently conducted. The results indicate that the sustainability scores for each dimension are as follows: ecology (83.29), technology (78.21), policy (81.31), and institutional (79.31), which suggest a very sustainable status. In contrast, the social dimension (60.19) is moderately sustainable, while the economic dimension (38.92) is classified as less sustainable. The average value of all these dimensions is 70.2, which can be considered quite sustainable. Within each dimension, there are sensitive attributes that are related to its sustainable status. These attributes are a key factor in the formulation of implementation strategies to encourage food security in Kediri District. The prospective analysis of the key factors indicates that most of these factors are situated in Quadrant II, signifying a high level of influence and dependence. To promote resilience effectively and efficiently in Kediri District, it is essential to prioritize strategies that consider the pivotal factors within Quadrant II.